Enhancing behavior change technique coding methods: Identifying behavioral targets and delivery styles in smoking cessation trials - Black, N; Williams, A; Javornik, N; Scott, C; Johnston, M; Eisma, M; Michie, S; Hartmann-Boyce, J; West, R; Viechtbauer, W; De Bruin, M (Oxford University Press, 2018)
Background The behavior change technique (BCT) taxonomy v1 is often used in systematic reviews for identifying active components of interventions. Its utility could be enhanced by linking BCTs to specific target behaviors and qualifying BCT delivery style. Purpose To determine whether behavioral targets and delivery styles of BCTs can be coded reliably and to determine the utility of coding these characteristics. Methods As part of a large systematic review of 142 smoking cessation trials, two researchers independently coded publicly and privately held intervention and comparator group materials, specifying the behavioral target (quitting, abstinence, medication adherence, or treatment engagement) and delivery style (tailored vs. not tailored; active participation vs. passive receipt) of each BCT. Results Researchers coded 3,843 BCTs, which were reliably attributed to behavioral targets (AC1 = 0.92, PABAK = 0.91). Tailoring (AC1 = 0.80, PABAK = 0.74) and participation (AC1 = 0.71, PABAK = 0.64) were also coded reliably. There was considerable variability between groups in quitting and abstinence BCTs (ranges: 0–41; 0–18) and in tailoring and participation (ranges: 0–20; 0–32), but less variability for medication adherence and treatment engagement (ranges: 0–6; 0–7). Conclusions Behavioral targets and delivery styles of BCTs can be reliably identified and occur with sufficient frequency in smoking cessation trials for inclusion in quantitative syntheses (e.g., meta-regression analyses). Systematic reviewers could consider adopting these methods to evaluate the impact of intervention components targeting different behaviors, as well as the benefits of different BCT delivery styles.